Presence and Possible Origin of ɛ(γ-Glutamyl)Lysine Isodipeptide in Human Plasma - Harsfalvi, J; Tarcsa, E; Udvardy, M; Zajka, G; Szarvas, T; Fesus, L (Thrombosis and Haemostasis, 1992)
ɛ(γ-glutamyl)lysine isodipeptide has been detected in normal human plasma by a sensitive HPLC technique in a concentration of 1.9-3.6 μmol/1. Incubation of in vitro clotted plasma at 37° C for 12 h resulted in an increased amount of isodipeptide, and there was no further significant change when streptokinase was also present. Increased in vivo isodipeptide concentrations were also observed in hypercoagulable states and during fibrinolytic therapy.